Adverse effect left congenital diaphragmatic hernia to position and function of the fetal heart - Pribadi, Adhi; Mose, Johanes Cornelius (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: There many heart problems in patients with CDH. Methods: Between January 2012 and July 2015, three pregnancies (1:2153) performed ultrasound examination to investigate suspected CDH. All symptoms displayed descriptively in table. Results: In prenatal life, ultrasonography has a high sensitivity for detection of congenital diaphragmatic hernia. The definite ultrasonographic diagnosis of fetal congenital diaphragmatic hernia lies on the visualization of abdominal organs in the chest. The ultrasonographic hallmark of this condition is a fluid-filled mass in same level with fetal heart. Ultrasonographic features indicative of congenital diaphragmatic hernia include polyhydramnios; an absent or intraabdominal stomach bubble, mediastinal-cardiac shift away from the side of the herniation and a small fetal abdominal circumference or growth retarded. The effect of stomach pressure results 100% the position of the heart and affect the effectiveness of the heart such as pressure on the heart resulting tamponade effect. Conclusions: Cardiac changes due to the insistence by CDH can lead to changes position, anatomical and cardiac function.